Pengaruh Rasio Ekuivalen terhadap Traveling Speed Stationary Flame pada Meso-scale Combustor dengan Sudden Expansion - Rachmad Dwi Fitriansyah; Digdo Listyadi Setyawan; Gaguk Jatisukamto (STATOR: Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
The flame on a meso scale combustor has different stability and speed levels according to the regime flame and its characteristics. This study aims to examine the effect of the equivalent ratio of LPG and air gas to the traveling speed stationary flame on a meso combustor with a sudden expansion. The research tool used is a combustor with a diameter of a sudden expansion of 6 mm and a length of 20 mm expansion, mixer and pisco tube channels. The research parameters include fuel discharge, air discharge and flame regime where the fuel and air discharge is varied to get the regime flame and its characteristics are traveling speed. Flame regime visualization by photo flame of video cut off per frame and then processed using video editing software to get traveling speed. The results showed that the observed stationary flame was stationary asymmetric downward at the equivalent ratio ф = 0.82 and ф = 0.86 and stationary symmetric in the equivalent ratio ф = 0.90 and ф = 0.95. The lowest equivalent ratio ф = 0.82 has traveling speed = 4.41 cm / s, and the highest equivalent ratio ф = 0.95 has a traveling speed = 16.68 cm / s. The equivalent ratio ф = 0.82 to ф = 0.95 in the stationary regime flame shows that the higher the equivalence ratio, the traveling speed also increases with the number reaching 16.68 cm / s. Keywords: Meso-scale combustor, traveling speed, stationary flame, sudden expansion,